Design and Development of an IoT-Based PDAM Water Bill Monitoring System for Private Homes - Wicaksono , Satria; Rizantha, Iqbal (Politeknik Negeri Padang, 2025)
This project focuses on developing an IoT-based water bill monitoring system for private homes using a NodeMCU ESP8266 microcontroller, a water flow sensor, and cloud integration via ThingSpeak. The system enables real-time monitoring of water usage, allowing users to control and reduce excessive consumption.Testing showed that the water flow sensor operated with high accuracy, despite minor discrepancies. Comparisons between the sensor’s output and actual measured water volumes revealed error rates ranging from 0.75% to 1.80% across different flow rates. The system also accurately calculated water bills using a predefined rate of IDR 7,000 per liter. For example, a water usage of 3 liters resulted in a bill of IDR 21,000, matching the expected amount. The system successfully provided real-time billing through the ThingSpeak platform and a custom mobile app developed with MIT App Inventor. Additionally, the built-in buzzer effectively alerted users when water usage exceeded predefined limits. While the system performed efficiently, occasional network instability affected IoT performance. Future improvements could focus on enhancing sensor accuracy and improving the user interface for better functionality.